2023
DOI: 10.1177/14680173231165928
|View full text |Cite
|
Sign up to set email alerts
|

Outreach to farmworkers before and during the COVID-19 pandemic

Abstract: Summary Outreach is an important element of social care. It is an informal but planned form of on-site service delivery to vulnerable populations. Outreach affects some target populations, such as migrant farmworkers, immensely. Outreach staff demonstrate a unique capacity to navigate remote and hard to -to-reach areas, making contact with farmworkers who would otherwise not receive essential services. This ethnographic study describes how organizations make first contact with farmworkers in normal times, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Internet‐based platforms, such as WhatsApp and Facebook, emerged as one of the primary forms of maintaining communication and disseminating health information to farmworkers during the pandemic. This finding aligns with limited research on outreach to farmworker communities in other states during this time period 9,21 . Shaver, however, emphasizes that telehealth should be a supplement for health care, not a replacement, 24 and community health workers' plans for future health education and outreach support this belief.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Internet‐based platforms, such as WhatsApp and Facebook, emerged as one of the primary forms of maintaining communication and disseminating health information to farmworkers during the pandemic. This finding aligns with limited research on outreach to farmworker communities in other states during this time period 9,21 . Shaver, however, emphasizes that telehealth should be a supplement for health care, not a replacement, 24 and community health workers' plans for future health education and outreach support this belief.…”
Section: Discussionsupporting
confidence: 61%
“…PPE provision might also have served to mitigate some of the well‐documented chronic health illnesses and structural vulnerabilities experienced among farmworker communities, which can be exacerbated by the virus spread 19,20 . Other studies have also reported that community health workers played critical roles in distributing PPE supplied from government aid packages to farmworkers 9,21 . In addition to a lack of access to PPE, large portions of the Hispanic population in the United States faced food insecurity during the pandemic 22 due to isolation, transportation issues, and economic hardship.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations